(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study explores ethnolinguistics and linguaculturology as two closely related subfields of linguistics that examine the dynamic relationship between language and culture. Ethnolinguistics focuses on how language reflects the worldview, traditions, and social practices of specific ethnic communities. Linguaculturology, in turn, emphasizes the mutual influence of language and culture within the framework of intercultural communication, highlighting culturally bound linguistic phenomena. Both disciplines contribute to understanding how language not only conveys information but also embodies cultural identity, values, and collective memory. The paper underscores the interdisciplinary nature of these fields and their relevance to translation studies, language teaching, and cross-cultural dialogue.